Solid state characterization of Cu-Zno nanocomposite synthesised via micro-wave irradiation - Aliyu, Hauwa Sidi; Abdullah, Abdul Halim; Abbas, Zulkifly (2014)
The preparation of Cu-ZnO nanocomposite with average crystallite size less than 70nm was carried out successfully using commercial microwave oven operated at a low temperature and pressure (900C and 240W) respectively; zinc acetate dehydrate and copper (II) nitrate were used as precursors and ethylenediamine tetracetic acid as complexing agent. Variationsof experimental conditions in the microwave such as total period of exposure and irradiation power were found to affect the nanostructures formation. Energy band gap of Cu-ZnO was estimated using absorption data obtained from UV-Vis spectrophoto meter. The prepared Cu-ZnO was characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM),Energy Dispersive X-ray (EDX) analysis.Spectra from XRD of Cu-ZnO nanocomposite revealed a hexagonal zincite phase structure and the average crystallites sizes were found to be within the range of TEM result. The XRF analysis revealed the actual elemental composition in the prepared sample. The microwave oven irradiation technique was found to be an effective synthetic method for the preparation of Cu-ZnO nanocomposites and the Cu metalwas found to be suitable for coupling with ZnO semiconductor nanoparticle photocatalysis.